Cognitive behavior therapy for Stuttering: A case series - Reddy R; Sharma M; Shivashankar N (Indian Journal of Psychological Medicine, 2010)
The present investigation was aimed at studying the efficacy of cognitive behavior therapy (CBT) in reducing the symptoms of stuttering and dysfunctional cognitions and in enhancing assertiveness and quality of life in clients with stuttering. Five clients with stuttering who met the inclusion criteria (male clients with diagnosis of stuttering) and exclusion criteria (clients with brian damage), substance abuse or mental retardation were enrolled for the study. A single-case design was adopted. The pre-, mid- and post-assessment were carried out using Stuttering Severity Scale (SSI), Perception of Stuttering Inventory (PSI), Beck′s Anxiety Inventory (BAI), Dysfunctional Attitude (DAS), Fear of Negative Evaluation (FNE), Assertiveness Scale (AS), Rosenberg′s Self-Esteem Scale (RSES), and World Health Organization - Quality of Life Scale (WHO-QOL). Five clients received cognitive behavioral intervention comprising of psycho-education, relaxation, deep breathing, humming, prolongation, cognitive restructuring, problem-solving strategies and assertiveness. At post-treatment assessment, there was improvement. The findings of the study are discussed in the light of available research work, implications, limitations of the study and suggestions for future research.